Molecular identification of Leishmania spp. isolates causes cutaneous leishmaniasis (CL) in Sanliurfa Province, Turkey, where CL is highly endemic - Gurses, Gulcan; Ozaslan, Mehmet; Zeyrek, Fadile Yıldız; Kılıç, Ibrahim H; Doni, Nebiye Yentür; Karagöz, I Didem; Uluca, Nermin (Folia microbiologica, 2018)
Cutaneous leishmaniasis (CL) is an important public health problem in Turkey. CL has been most frequently seen in Sanliurfa. There is an expectation of increase in the population of leishmaniasis cases with the influence of Syrian refugees arriving in Turkey. In this study we aimed to diagnosis of CL and identifying of parasite from Leishmania isolates by using ITS 1 PCR RFLP. Samples were collected from 135 CL patients in Sanliurfa. After the specimens were inoculated in medium NNN, the ones which were cultures positive were cultivated in RPMI 1640 followed by PCR-RFLP. Genomic DNA was extracted phenol-chloroform procedure. Samples were examined by using ITS 1 PCR followed by RFLP analysis. Our results indicated that two species, L. tropica (132 samples) and L. major (3 samples), are responsible for cutaneous leishmaniasis in Sanlıurfa. Our study is the first scientific study in which it is reported molecular analyses of cutaneous leishmaniasis cases caused by L. major in Sanliurfa in Southestern Anatolia Region. Because CL cases caused by L.major are detected in our study, it is considered that genotyping is important for diagnosis of Leishmania and following change of epidemiology.
Keywords: polymerázová řetězová reakce; DNA, Protozoan; polymorfismus délky restrikčních fragmentů; lidé; mladiství; Turecko; Adult; Middle Aged; Leishmania; Turkey; Infant; Female; dítě; DNA, Ribosomal Spacer; Adolescent; Humans; Polymerase Chain Reaction; protozoální DNA; Leishmaniasis, Cutaneous; Skin; předškolní dítě; leishmanióza kožní; lidé středního věku; Child, Preschool; Polymorphism, Restriction Fragment Length; mužské pohlaví; mladý dospělý; kůže; ženské pohlaví; Young Adult; Male; Aged; Child; dospělí; mezerníky ribozomální DNA; kojenec; senioři